2001
DOI: 10.1089/089771501750055802
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Lecithinized Superoxide Dismutase and Methylprednisolone on Spinal Cord Injury in Rats: Transcriptional Regulation of Inflammatory and Neurotrophic Genes

Abstract: The effects of lecithinized superoxide dismutase (PC-SOD) and/or methylpredisolone (MP) in preventing secondary pathological changes after spinal cord injury (SCI) were investigated in rats with reference to recovery of hindlimb motor function and expression of mRNA of pro-inflammatory and neurotrophic genes. Hindlimb motor function was assessed as the BBB open field locomotor scores. The BBB scores of three groups treated with either PC-SOD (40,000 units/kg), MP (30 mg/kg), or a combination of PC-SOD and MP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…PC-SOD has been shown to protect endothelial cells in in vitro studies, 15,16 and it also has anti-inflammatory properties. 17 The results of the present study suggest that PC-SOD provides neuronal protection by antiapoptotic mechanisms. PC-SOD increased the mitochondrial levels of antiapoptotic Bcl-2 protein and decreased the subsequent cytosolic translocation of cytochrome c, thus attenuating the downstream caspase activation.…”
Section: Discussionsupporting
confidence: 52%
“…PC-SOD has been shown to protect endothelial cells in in vitro studies, 15,16 and it also has anti-inflammatory properties. 17 The results of the present study suggest that PC-SOD provides neuronal protection by antiapoptotic mechanisms. PC-SOD increased the mitochondrial levels of antiapoptotic Bcl-2 protein and decreased the subsequent cytosolic translocation of cytochrome c, thus attenuating the downstream caspase activation.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it is worth noting in conclusion that a number of animal studies have suggested that PC-SOD is also effective in the treatment of these conditions (Tamagawa et al, 2000;Chikawa et al, 2001;Nakajima et al, 2001;den Hartog et al, 2004;Tsubokawa et al, 2007). Thus, the results obtained in this paper should provide useful evidence when considering the most appropriate clinical protocol for therapeutic administration of PC-SOD against these diseases.…”
Section: Pc-sod-and Dss-induced Colitis 161mentioning
confidence: 65%
“…MPSS did not reduce astrogliosis. Studies have shown that MPSS inhibits the expressions of several cytokines (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…This therapy is based on reported improvements in neurological recovery in humans and laboratory animals (7,13,14,52,51) and by its reduction in early pathophysiological events and macrophage infiltration (46,53,54 The effects of MPSS on spinal cord injury may depend on the dose, the timing of treatment, the duration of treatment, and the spinal cord injury model used (55). Although MPSS has been shown to reduce the expression of inflammatory cytokines, downregulate lipid peroxidation in the spinal cord and reduce the density of ED-I-positive macrophages or/and microglia at the first 2 days after contusion (46,56), significant functional recovery associated with these biochemical or histological changes was not observed.…”
Section: Discussionmentioning
confidence: 99%